2005
DOI: 10.4103/0019-5359.18964
|View full text |Cite
|
Sign up to set email alerts
|

Tilt-table testing as a predictor of + GZ tolerance

Abstract: BACKGROUND: G-tolerance assessment is an essential element of both military pilot and pilot candidate evaluation. AIMS: Attempt at prediction of individual relaxed + Gz tolerance on the basis of head-up tilt (HUT) testing. SETTINGS AND DESIGN: In two stages, 20 healthy men at the mean age 21.5 years took part in this study. The first stage, a 45 min, HUT test was performed using the Westminster protocol. During the second stage each underwent a centrifuge evaluation in response to gradual onset rate profiles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…levels below 1g lead to inferior results, and g levels above 1g do not seem to produce considerable benefits, but increase knee joint moments and might not tolerated as well, as anecdotal evidence from one participant with a pre-syncope at 1.5g suggests and literature confirms for higher g-levels [18]. Whether a longer familiarization period in the centrifuge would allow participants to develop a movement pattern that is closer to the natural one, resulting in higher peak forces, has to be answered in a future training study.…”
Section: Plos Onementioning
confidence: 96%
“…levels below 1g lead to inferior results, and g levels above 1g do not seem to produce considerable benefits, but increase knee joint moments and might not tolerated as well, as anecdotal evidence from one participant with a pre-syncope at 1.5g suggests and literature confirms for higher g-levels [18]. Whether a longer familiarization period in the centrifuge would allow participants to develop a movement pattern that is closer to the natural one, resulting in higher peak forces, has to be answered in a future training study.…”
Section: Plos Onementioning
confidence: 96%
“…In addition, due to mechanical force and severe hemodynamic changes, cardiomyocytes and muscle fibers will suffer from some damages. Some authors have confirmed the effects of high +Gz were similar to hemodynamic changes observed in ischemia reperfusion (I/R) [ 12 ].…”
Section: Introductionmentioning
confidence: 81%
“…It was observed that the four of those tested who demonstrated vasovagal syncope during the tilt test had a G z -level tolerance from 1 4 to 1 8.1 G, which was comparable to the group without any syncope. Nobody lost consciousness during the centrifuge testing ( 14 ).…”
Section: Discussionmentioning
confidence: 99%